The emergence of the exciting new Web 3.0 and the future of open educational resources - Bidarra, José (2007)
There is a general idea that video games can teach skills that are important in today’s society, namely: analytical thinking, construction of hypotheses, development of strategies, creativity, team building, multitasking, decision making and problem solving. This idea frequently extends to situations that involve some kind of stress and require fast decisions. On the other hand, there is a perception that e-learning can benefit from video games, specially because they can make complex subjects more interesting and are able to cope with up-and-coming learning profiles. Avatar-based worlds, such as Second Life, possibly will provide for a richer, more effective and more enjoyable experience for students. The materialization of the so-called Web 3.0 (Second Life, Divvio, Joost and VRML/X3D worlds) following the mainstream collaborative and social Web 2.0 (MySpace, Pandora, YouTube), seems to be marked by this mix of humanlike avatars, intelligent agents and rich multimedia features that live happily within interactive 3D environments. No matter how interesting this may be for education, more research and practical experience are needed to make clear which features of games and 3D worlds are more important for nowadays learning and in what ways we can test students on the skills they actually learn. This paper investigates emergent experiences involving multimedia, video games and 3D environments freely available on the Web, and explores new ways to make e-learning more effective in the future realm of Open Educational Resources.